China-Africa and an Economic Transformation - Oqubay, Arkebe; Lin, Justin Yifu (Oxford University Press, 2019)
Progress in Africa's economic growth in the new millennium has been uneven across countries, and has not translated into structural transformation. The same can be said about the evolving China-Africa economic relations. Although economic ties between China and Africa have made a positive contribution, the impact of this dynamic engagement has been uneven, shaped by variations in strategic approach, policy ownership, and implementation capacity among African governments. As China undergoes major economic rebalancing to upgrade to an innovation-driven economy, this is bound to affect China-Africa relations, offering both opportunities and challenges. Authored by leading scholars on Africa, China, and China-Africa relations, this volume brings together stimulating and thought-provoking perspectives, and deeper analyses on the evolving China-Africa relations. Focusing on Africa's economic development, the volume looks at core areas of structural transformation: productive investment and industrialization, international trade, infrastructure development, and financing. China-Africa relations are considered in the context of the global division of labour and power, and the particular role of both China and the continent of Africa in the evolving global hierarchy. This volume seeks to fill the gap in the existing literature, steer policy and scholarly debate on the progress and trajectory of China-Africa cooperation, and analyse China's development path as a source of learning for Africa.